DAMPAK HUKUM ASAS KELEMBAGAAN ATAU PEJABAT PEMBENTUK YANG TEPAT DALAM PEMBENTUKAN PERDES - Tri Laksono, Wibowo; Achmad Affandi, Rizal; Estu Bagijo, Himawan (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2024)
The formation of village regulations that comply with the principles of appropriate forming officials is important to ensure the legitimacy and compliance of village communities. However, this process formation various problems. Problems in this research (1) What is the mechanism for forming village regulations that fulfill the principles of appropriate forming officials? (2) What are the legal impacts of forming village regulations that do not meet the principles of appropriate forming officials? This type of research uses normative law with a statutory and conceptual approach. Collecting legal materials uses literature study, and analyzes using qualitative descriptive. Research results: (1) The formation of village regulations has the same mechanism as the formation of statutory regulations, which includes planning, drafting, discussion, ratification or stipulation, and promulgation, (2) Village regulations do not meet the institutional principles or appropriate forming officials has the impact of formal defects, administrative disruption, potential abuse of power, and creates legal uncertainty. Moreover, village regulations that do not meet the appropriate institutional principles or forming officials can create a risk of non-compliance with village regulations so that village regulations do not run effectively. Keywords: principles of appropriate forming officials, village regulations, challenges in forming village regulations, legal impact